Autonomy and subsidiarity: Kantian roots of David Held’s cosmopolitism - Moya, Eugenio (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The cosmopolitan principles (specially, autonomy and subsidiarity) are, according to Held, principles that can be universally shared and can currently form the basis for the protection and nurturing of each person’s equal interest in the determination of the democratic institutions that govern their lives. They are principles that force us, in addition, to defend a multilevel governance and pooling sovereignties that bring political decisions closer to the affected. This article analyzes, precisely, the philosophical and political implications of this onion model of cosmopolitanism and traces its Kantian roots.
Keywords: autonomy; cosmopolitanism; democracy; state; globalization; Held; Kant; Subsidiarity